Material Approaches to Roman Magic : Occult Objects and Supernatural Substances - Parker, Adam (TRAC Themes in Roman Archaeology Ser, 2018)
Cover -- Book Title -- Copyright -- Contents -- Series Foreword: Sergio González Sánchez -- 1. Introduction: Materials, Approaches, Substances, and Objects: Stuart McKie and Adam Parker -- 2. The Medium Matters: Materiality and Metaphor in Some Latin Curse Tablets: Celia Sánchez Natalías -- 3. Phallic Magic: A Cross Cultural Approach to Roman Phallic Small Finds: Alissa Whitmore -- 4. Little Bottles of Power: Roman Glass Unguentaria in Magic, Ritual, and Poisoning: Thomas Derrick -- 5. Victory of Good over Evil? Amuletic Animal Images on Roman Engraved Gems: Idit Sagiv -- 6. 'The Bells! The Bells!' Approaching Tintinnabula in Roman Britain and Beyond: Adam Parker -- 7. Rubbing and Rolling, Burning and Burying: The Magical Use of Amber in Roman London: Glynn Davis -- 8. Linking Magic and Medicine in Early Roman Britain: The 'Doctor's' Burial, Stanway, Camulodunum: Nicky Garland -- 9. The Archaeology of Ritual in the Domestic Sphere: Case Studies from Karanis and Pompeii: Andrew Wilburn -- 10. The Legs, Hands, Head and Arms Race: The Human Body as a Magical Weapon in the Roman World: Stuart McKie -- 11. Amulets, the Body and Personal Agency: Véronique Dasen -- Back Cover.